Rumen fermentative metabolomic and blood insights into the effect of yeast culture supplement on growing bulls under heat stress conditions - Zhang, Xian; Liang, Huan; Xu, Lanjiao; Zou, Bicheng; Zhang, Tingzhou; Xue, Fuguang; Qu, Mingren (Frontiers in Microbiology, 2022)
This study was conducted to investigate the effects of yeast culture supplements on the physiological state and growth performance of growing bulls under heat stress conditions and the underlying mechanism. A total of 14 (6.0 ± 1.0 months old) growing bulls with similar body weight were randomly assigned into the control group (YC0g/d) and yeast culture supplement group (YC40g/d). YC0g/d contained three replicates, with two bulls in each replicate, which were fed a basal diet. Meanwhile, the YC40g/d treatment contained four replicates, with two bulls in each replicate, which were fed a basal diet supplemented with 40 g/day of yeast culture per cattle. Growth performance, nutrient digestibility, rumen fermentable metabolites, serum immunity, serum hormones, and serum antioxidant parameters were measured. Results showed that the average daily gain significantly increased (P < 0.05), while the feed-to-gain ratio significantly decreased (P < 0.01) after YC supplementation compared with the YC0g/d. The digestibility of neutral detergent fiber (P < 0.05) was higher in YC40g/d. There were no significant differences in ruminal pH, NH3-N, butyrate, or acetate/propionate (P > 0.05). Besides, the rumen MCP, acetate, propionate, and total VFA content remarkably increased with the supplement of YC (P < 0.05). Yeast culture supplementation increased the concentration of nicotinamide riboside, neuromedin B, peptides, and formyl-5-hydroxykynurenamine. The YC40g/d group had a significantly (P < 0.05) higher serum triiodothyronine level, serum glutathione peroxidase levels, and total antioxidant capacity while having a lower serum malondialdehyde level than the YC0g/d group. In conclusion, the addition of yeast culture in the diet improves the growth performance of growing bulls under heat stress by increasing nutrient digestibility, rumen fermentation function, antioxidant capacity, and rumen metabolites.